The Effect of Slurry Erosion Wear on Boronized Ductile Iron - Abdullah, Bulan; Yusof, Khalissah; Zarr Ahmad Bakhtiar, Abu; Hayati Saad, Nor (International Journal of Engineering and Technology, 2018)
In this study, the effects of boronizing on slurry erosion wear properties of ductile iron were investigated. Specimens were boronized at temperatures of 850ÂºC, 900ÂºC and 950ÂºC for 8 hours and self-cooled in the furnace until reached the room temperature. Boronizing paste were used as a medium in this process. Â The specimens were analyzed using optical microscope (IMAPS Software) and Vickers Microhardness tester to find thickness and microhardness of boride layer respectively. Slurry erosion wear test were performed to define the weight loss. As a result, the hardness of boride layers was measured in the range of 454 HV0.10 â€“ 1023 HV0.10. Furthermore, the wear resistance of boronized temperature at 950ÂºC is higher than the samples at temperature 900ÂºC, 850ÂºC and untreated sample. It can be concluded that the higher the heating temperature will result in higher wear resistance of boronized ductile iron.Â Â